2022
DOI: 10.1021/acssensors.2c00943
|View full text |Cite
|
Sign up to set email alerts
|

Selective Translocation of Cyclic Sugars through Dynamic Bacterial Transporter

Abstract: The selective translocation of molecules through membrane pores is an integral process in cells. We present a bacterial sugar transporter, CymA of unusual structural conformation due to a dynamic N terminus segment in the pore, reducing its diameter. We quantified the translocation kinetics of various cyclic sugars of different charge, size, and symmetry across native and truncated CymA devoid of the N terminus using singlechannel recordings. The chemically divergent cyclic hexasaccharides bind to the native a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…This data at low salt buffer indicates weak electrostatic interaction of D9 peptides with few positively charged residues at the trans side of the pore as opposed to no D9 binding at high salt buffer, confirming the salt‐dependent charge screening effect. The addition of R9 peptides to the same pore produced well‐defined ion current blockages and this competitive binding of D9 and R9 peptides confirmed the charge‐selective translocation of cationic peptides through the CymA pores in agreement with the cation‐selective nature of the pore (Figure 4c) [47,49] …”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…This data at low salt buffer indicates weak electrostatic interaction of D9 peptides with few positively charged residues at the trans side of the pore as opposed to no D9 binding at high salt buffer, confirming the salt‐dependent charge screening effect. The addition of R9 peptides to the same pore produced well‐defined ion current blockages and this competitive binding of D9 and R9 peptides confirmed the charge‐selective translocation of cationic peptides through the CymA pores in agreement with the cation‐selective nature of the pore (Figure 4c) [47,49] …”
Section: Resultssupporting
confidence: 60%
“…Previous studies have shown that CymA is naturally evolved for the selective uptake of six‐fold symmetric cyclic hexasaccharide, which binds to specific charged residues in the pore with high binding affinity [47,49] . This pore has a unique N terminal segment that has not been resolved by X‐ray crystallography due to its dynamic nature and its role in sensing is uncertain [46] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations